ANALISIS PROFITABILITAS PEMBANGUNAN PERUMAHAN PADA PT. SEJAHTERA LESTARI - Halmu, Muhammad (EKONOMIA, 2013)
Advantages acquisition is a very important tool for obtaining information regarding the financial position. To assess the financial performance of a business venture, required some specific benchmarks or standards. The standard can be either historical comparison or financial comparison with the financial data in the prior year period. Without such a comparison, will not be known whether the performance of a task force showed increased or decreased.From the description that has been previously described problems can be formulated as follows: